2015
DOI: 10.1155/2015/698738
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Mechanical, and Thermal Analysis of Polylactic Acid/Fumed Silica/Clay (1.28E) Nanocomposites

Abstract: Polylactic acid/fumed silica/clay (PLA/FS/clay) (1.28E) nanocomposites have been successfully prepared by solution-intercalation film-casting technique. The resultant nanocomposites were characterized by Fourier Transform Infrared Spectroscopy (FT-IR), Scanning Electron Microscopy (SEM), tensile test, thermogravimetric analysis (TGA), and moisture absorption test. The FT-IR spectrum indicated that PLA/FS/clay with 2 wt% had much broader peak compared to 5 wt%, 10 wt%, and 15 wt% nanocomposites. Incorporation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Better results were obtained for unmodified sepiolite in contrast to the organically modified sepiolite (Liu et al 2012). A DSC study on PLA-fumed silica (FS)-clay nano composite revealed that addition of 2 wt% clay to PLA FS composite increased the thermal stability and reduced the moisture weight percentage (Lai et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Better results were obtained for unmodified sepiolite in contrast to the organically modified sepiolite (Liu et al 2012). A DSC study on PLA-fumed silica (FS)-clay nano composite revealed that addition of 2 wt% clay to PLA FS composite increased the thermal stability and reduced the moisture weight percentage (Lai et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, PLA/CTAC-MMT 0.5 wt.% and PLA/O_MMT 1.0 wt.% composites showed a rise in tensile strength by 36% and 44%, correspondingly. The rise in the tensile strength of PLA can be ascribed to the interactions developed between the surface silanol groups and PLA chains [64,65]. 10 that all samples show a transition peak in the temperature range of 50-60 • C (Stage 1), which is related to the glass transition of the PLA and PLA/CTAC-MMT composites.…”
Section: Mechanical Testingmentioning
confidence: 90%
“…However, Ogata et al (1997) Likewise, a lot of publications have been widely reported on PLA/silica nanocomposites preparation and properties (Basilissi et al, 2013a;Chang et al, 2015;Dorigato et al, 2012;Fukushima et al, 2011;Gong et al, 2014;Lai and Hsieh, 2016;Murariu et al, 2015;Pilić et al, 2015;Wang et al, 2006;Wang et al, 2008a;Wen et al, 2009;Wen et al, 2011;Yan et al, 2007b;Zhang et al, 2008a;Zhu et al, 2010). For instance, Yan et al (2007b) initially prepared nanosilica grafted with lactic acid prior to the modified silica being melt blended with PLA matrix to enhance the interfacial interactions.…”
Section: Polylactide Based Nanocompositesmentioning
confidence: 99%